PENGARUH PENGALAMAN KERJA, INDEPENDENSI, INTEGRITAS, OBYEKTIVITAS DAN KOMPETENSI TERHADAP KUALITAS AUDIT - Wardhani, Veby Kusuma; Triyuwono, Iwan; Achsin, Muhammad (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
This study is specifically to evaluate the effect of work experience, independence, integrity, objectivity and competence toward the audit quality. This study was conducted by distributing questionnaires to KAP in Malang. By counting related association division of KAP, the number of sample in this study was 63 respondents who definitely worked in 7 KAP. This research is a quantitative study. The sample was chosen by using purposive sampling. The hypothesis test used multiple linear regressions in SPSS version 16. All variables in this study were measured using Likert Scale. The results shows that all independent variables have positive effect toward audit quality. The partial influence (T-test) showed that the variables of work experience, Independence, Integrity, Objectivity, Competence affect audit quality. In the other hands, the simultaneous effect is shown by the value of R2 from 75.2 %. It was shown by work experience, independence, integrity, objectivity, and competence which affecting audit quality changing of 75.2% and the rest, 24.8 % in audit quality changing, is affected by other variables which is not investigated in this study